Clinical, neuroimaging, and molecular spectrum of TECPR2‐associated hereditary sensory and autonomic neuropathy with intellectual disability. Issue 6 (11th May 2021) - Neuser, Sonja; Brechmann, Barbara; Heimer, Gali; Brösse, Ines; Schubert, Susanna; O'Grady, Lauren; Zech, Michael; Srivastava, Siddharth; Sweetser, David A.; Dincer, Yasemin; Mall, Volker; Winkelmann, Juliane; et al.
Abstract: Bi‐allelic TECPR2 variants have been associated with a complex syndrome with features of both a neurodevelopmental and neurodegenerative disorder. Here, we provide a comprehensive clinical description and variant interpretation framework for this genetic locus. Through international collaboration, we identified 17 individuals from 15 families with bi‐allelic TECPR2 ‐variants. We systemically reviewed clinical and molecular data from this cohort and 11 cases previously reported. Phenotypes were standardized using Human Phenotype Ontology terms. A cross‐sectional analysis revealed global developmental delay/intellectual disability, muscular hypotonia, ataxia, hyporeflexia, respiratory infections, and central/nocturnal hypopnea as core manifestations. A review of brain magnetic resonance imaging scans demonstrated a thin corpus callosum in 52%. We evaluated 17 distinct variants. Missense variants in TECPR2 are predominantly located in the N‐ and C‐terminal regions containing β‐propeller repeats. Despite constituting nearly half of disease‐associated TECPR2 variants, classifying missense variants as (likely) pathogenic according to ACMG criteria remains challenging. We estimate a pathogenic variant carrier frequency of 1/1221 in the general and 1/155 in the Jewish Ashkenazi populations. Based on clinical, neuroimaging, and genetic data, we provide recommendations for variant reporting, clinical assessment, and surveillance/treatment of individuals with TECPR2 ‐associated disorder. This sets the stage for future prospective natural history studies.